The Concept of Digital Rupiah (Central Bank Digital Currency) as a Medium of Exchange in the Context of Sharia Economic Law - Muhammad Fakhriel Zayida; Didah Durrotun Naafisah; M. Asro; M. Anton Athoillah (Jurnal Hukum Ekonomi Syariah, 2025)
The development of digital technology has prompted central banks to develop Central Bank Digital Currency (CBDC), including in Indonesia with the introduction of Digital Rupiah. Although it has been legally recognized through Law Number 4 of 2023 concerning the Development and Strengthening of the Financial Sector (P2SK Law), its compatibility with Sharia Economic Law is still being debated. Therefore, this study aims to analyze the Digital Rupiah as a medium of exchange from the perspective of Islamic Economic Law, particularly in relation to public interest and the objectives of Sharia law. This study employs a descriptive-analytical qualitative method with a normative approach, examining relevant regulations and comparing the concept of the Digital Rupiah with principles in Islamic Economic Law based on literature reviews from academic sources, scientific journals, and official documents from the Bank of Indonesia. The results of the study indicate that the Digital Rupiah is consistent with the objectives of Sharia law, particularly in terms of hifzh al-mal (preserving wealth) through value stability and hifzh al-aql (preserving intellect) through transaction transparency and technology-based financial inclusion. Additionally, the Digital Rupiah enhances hifzh an-nafs (preserving life) through a safer financial system. The Digital Rupiah can be accepted under Islamic Economic Law, provided its implementation remains within the framework of justice, public interest, and is free from riba gharar and maisir. However, there are still several challenges faced by the Digital Rupiah, such as the need for further regulation regarding distribution, ownership, user protection, transaction mechanisms, and conversion, the need for digital security updates, and educating the public to ensure optimal distribution and usage.